Work, family and women's well-being : the influence of culture - Noor, Noraini M.; Mohd Mahudin, Nor Diana (Thomson, 2005)
This chapter examines work and family roles in relation to women 5 wellbeing. However, the emphasis is on the influence ofculture on how work and family roles are perceived and practiced, and the resulting implications for women 5 well-being. With the increase in the number ofwomen in the Malaysian workforce, the extent to which cultural values and practices may affect this relationship needs to be considered. The paper starts by providing an overview of the literature on women 5 roles and well-being, followed by research in Malaysia on the position ofwomen in Malaysian society and a description of typical contemporary women. As culture defines the appropriate roles ofmen and women, this gendered ideology is considered within the context of the Malays and Chinese, with probable implications for their well-being. Finally, several recommendations are proposed to take into account womens changed experiences, expectations and contexts